Criminal Liability for The Provision of Illegal WIFI Telecommunications Services - Kenza Radhya Ersa Atmawijaya, Muhammad; Eliakim Siringoringo, Dicky; Ricoras, Frans; Daniel Nainggolan, Rabin; Bagaskara Gunadi Putra, Satrio (Universitas Negeri Semarang (UNNES), 2023)
The impact of globalization and the rapid development of telecommunications technology has implications for changes in the operation and perspective of telecommunications, especially in the provision of Wi-Fi telecommunications services (ISP). The survey carried out by the Indonesian Internet Service Providers Association (APJII) Indonesia has reached 77.02% or the total population connected to the internet is 210,026,769 of the total population of 272,682,600 Indonesians in 2021. Along with the development of technology, of course It is undeniable that there will be potential violations or disobedience from people who do not comply with the provisions of laws and regulations so that they violate the rights of other communities. The rise of ISP and unlicensed or illegal Wi-Fi resellers has caused losses not only to the community but also to the national economy. Lack of understanding regarding licensing results in ISPs being subject to administrative sanctions to imprisonment. The purpose of this study is to find out how criminal liability for the operation of illegal Wi-Fi telecommunications services.